754 Farm mapping to assist, protect, and prepare emergency responders (farm mapper). (1st September 2016) - Keifer, Matthew; Weichelt, Bryan; Minor, Gerald; Reyes, Iris; Bendixsen, Casper
Abstract : Background: Farm Mapping to Assist, Protect and Prepare Emergency Responders (Farm MAPPER) is an interactive web-based tool developed by the NFMC that provides emergency responders onsite information about hazards, resources and physical layouts of agricultural operations. Emergency responders generally do not have right of entry to private farms to map them for future emergencies. Farm MAPPER provides a palate of icons representing items important in emergency events such hazards, access points, water sources, etc., even information on special needs farm residents. Methods: The system was developed to allow a farmer to drag and drops icons on an overhead farm map using their computer. Through Farm MAPPER this information is accessible to emergency responders in the fire station, in-route by web connected device, or onsite using QR codes located on post box posts. This knowledge assists responders to efficiently and safely respond to on farm emergencies. MAPPER presently displays icons on Bing maps in an overhead bird's eye view of the farm. Results: The team developed and tested the prototype Farm MAPPER application with local farmers and conducted mock response with the Pittsville fire department using the MAPPER on a volunteer farms. Feedback was received from both groups. Farmers found it easy to use and expressed willingness to map their farms for the benefit of the emergency responders who might use the application. Emergency responders who participated in the mock responses found the application helpful in quickly locating the items that they needed to avoid or employ for their safety and response efficiency. They suggested modifications to the application which have since been incorporated. Conclusions: The system was developed to handle geographic diversity, and will be available for worldwide adoption. The team is currently seeking collaborative opportunities to further expand the project reach beyond central Wisconsin.